DIAGNOSIS OF TREATMENT IN CASES OF LIVER FAILURE AND COMATOSE DISORDERS - Qirgizova Kholida Khudayberdiyevna (Western European Studies, 2024)
This article provides an in-depth exploration of the diagnostic and therapeutic approaches in cases of liver failure and comatose disorders. It outlines the clinical significance of timely and accurate diagnosis and the integration of multidisciplinary treatment strategies. The paper discusses advancements in diagnostic tools and treatment methodologies, presenting findings from recent studies and clinical experiences.
Keywords: Liver failure; comatose disorders; diagnosis; treatment